Pengaruh Slow Deep Breathing Terhadap Kelelahan Pada Pasien Gagal Ginjal Di Ruang Hemodialisis Di Rumah Sakit Murni Teguh Tuban Bali - Purwati, Diah; Wahyu, Afnijar (Pustaka Galeri Mandiri, 2025)
The hemodialysis therapy process which takes 4-5 hours, will generally cause fatigue. Overcoming this impact can be given slow deep breathing where relaxation is realized to regulate breathing deeply and slowly and one of the therapies that has proven its effectiveness to overcome fatigue. To determine the Effect of Slow Deep Breathing on Fatigue in Kidney Failure Patients in the Hemodialysis Room of the Murni Teguh Tuban Bali Hospital. This study used a pre-experimental design with a pre-test and post-test one group design. The sampling technique used total sampling of 16 respondents. Data were collected with FACIT questionnaire. Data were analyzed with Wilcoxon test. The results showed fatigue in patients with kidney failure before being given slow deep breathing the majority experienced overwhelm as many as 10 people (62.5%) and there was a change in fatigue after being given slow deep breathing to the majority not overwhelmed as many as 12 people (75%). Analysis of the Effect of Slow Deep Breathing on Fatigue in Renal Failure Patients in the Hemodialysis Room of the Pure Teguh Tuban Bali Hospital based on the Wilxocon test obtained a p-value of 0.014. The conclusion of this study is that there is an effect of slow deep breathing on fatigue in patients with kidney failure in the Hemodialysis Room of the Pure Teguh Tuban Bali Hospital.